أثر جودة الحياة الوظيفية في ترقية الأداء الوظيفي : دراسة حالة جامعة إفريقيا العالمية للفترة من 2013 إلى 2018 - الطيب، عبدالله عبدالخالق (جامعة حسيبة بن بوعلي الشلف - مخبر نظرية اللغة الوظيفية, 2019)
The purpose of this study is to identify the impact of quality career upgrade functionality, by measuring the functional factors of career planning and job security, and equilibrium between personal and financial factors. Follow the descriptive researcher for relevance to the nature and objectives of the study. Use the researcher survey tool to collect information. Represent a Community administrative researcher of the International University of Africa (700), the researcher picked a random sample consisting of (131) to represent the research community. Data is entered into the statistical package for the social sciences programme SPSS for analysis, where it was averaging and test (t) T-test and standard weights account to verify the hypotheses of the study. Int reached a number of conclusions the most important career factors-both career and job security design-affect upgrade performance in International University of Africa. As well as the process of balance between career and personal life had a positive impact on job performance upgrade in International University of Africa. As the study found that financial factors played a great role in upgrading the functionality in International University of Africa. Based on the results of the study the researcher made a number of recommendations and prepare a comprehensive plan for assessing, developing and improving the quality of performance at all levels, depending on the model of standards with the commitment of all groups of departments and divisions to carry out the evaluation programme. And working to organize the working relations and personal relationships between employees to achieve personal and career life balance, for its positive effect on upgrade functionality. And maintaining the existing level of financial evaluation in University and work to improve to achieve the desired job satisfaction among workers at the University, which would improve performance in General.
هدفت الدراسة إلى التعرف على أثر جودة الحياة الوظيفية في ترقية الأداء الوظيفي، وذلك من خلال قياس أثر العوامل الوظيفية المتمثلة في التخطيط الوظيفي والأمان الوظيفي، والاتزان بين الشخصية، والعوامل المالية. وقد اتبع الباحث المنهج الوصفي لملاءمته لطبيعة الدراسة وأهدافها واستخدم الباحث الاستبانة أداة لجمع المعلومات، وتمثل مجتمع البحث في أعضاء هيئة التدريس بجامعة إفريقيا العالمية والبالغ عددهم (615)، اختار الباحث عينة عشوائية مكونة من (131) فرداً لتمثيل مجتمع البحث. تم إدخال البيانات في برنامج الحزمة الإحصائية للعلوم الاجتماعية SPSS لتحليلها، حيث تم حساب المتوسطات وإجراء اختبار (ت) T-test وحساب الأوزان المعيارية للتحقق من فرضيات الدراسة. وقد توصل الباحث إلى عدد من النتائج أهمها أن العوامل الوظيفية – بشقيها التصميم الوظيفي والأمان الوظيفي – تؤثر في ترقية الأداء الوظيفي بجامعة إفريقيا العالمية، كذلك أن لعملية التوازن بين الحياة الشخصية والوظيفية أثر إيجابي في ترقية الأداء الوظيفي بجامعة إفريقيا العالمية. كما توصلت الدراسة إلى أن للعوامل المالية دور كبير في ترقية الأداء الوظيفي بجامعة إفريقيا العالمية. بناء على نتائج الدراسة قدم الباحث عدداً من التوصيات، وهي إعداد خطة شاملة لتقييم وتطوير وتحسين جودة الأداء على المستويات كافة، وذلك اعتماداً على نموذج من المعايير مع التزام جميع فئات العاملين بالإدارات والأقسام لتنفيذ برنامج التقييم، والعمل على تنظيم علاقات العمل والعلاقات الشخصية بين العاملين بما يحقق توازن الحياة الشخصية والوظيفية؛ لما لذلك من تأثير إيجابي على ترقية الأداء الوظيفي، والحفاظ على مستوى التقييم المالي القائم حالياً في الجامعة، والعمل على تحسينه بما يحقق الرضا الوظيفي المطلوب لدى العاملين بالجامعة، والذي من شأنه تحسين الأداء بصورة عامة.
Keywords: السياسة التعليمية -- البرامج التعليمية -- الوسائل التعليمية -- طرق التدريس -- التعليم الجامعي -- طلاب الجامعات -- الأداء الوظيفي -- الترقية -- جامعة إفريقيا العالمية -- أعضاء هيئة التدريس -- الحياة الوظيفية -- الجودة الشاملة -- الخرطوم -- السودان